Implementasi Sistem Informasi Akuntansi Pada Sekolah Terpadu Gema Nurani - Panca Indah Lestari; Sabar Hana DwiPutra; Kresno Murti Prabowo; Gugi Tyas (STMIK IKMI Cirebon, 2021)
Integrated Islamic Schools as a resource for science and technological advancements play an important role in concept development and implementation in IT units, especially those required to quickly solve system and data problems. Gemanurani Integrated Islamic School is a private school in Bekasi that focuses on Islamic education and has 25 school programs. The annual accounting reporting process at the Gemanurani School demands a good and useful information system as a monitoring of the foundation's wealth to determine management decisions in all teaching and learning activities. Along the way, it encountered obstacles such as undocumented cash flows, income returns, and annual tax reporting which had an impact on the slow completion of requests for household needs for each school unit. With an accounting information system, it will produce an overview of school household budget planning that focuses on data, applications and technology in the orientation of business needs.